The five horsemen of the modern world : climate, food, water, disease, and obesity - Callahan, Daniel, 1930-2019 (Columbia University Press, 2016)
In recent decades, we have seen five perilous and interlocking trends dominate global discourse: irreversible climate change, extreme food and water shortages, rising chronic illnesses, and rampant obesity. Why can?t we make any progress in counteracting these problems, despite vast expenditures of intellectual, institutional, and societal capital? What makes these global emergencies the "wicked problems" that resist our best efforts and only grow more daunting? Daniel Callahan, noted author and the nation?s preeminent scholar in bioethics, takes a cross-cutting look at these global problems and shines a light on the institutions, practices, and actors that block major change. We see partisan political and ideological forces, old fashioned hucksters, and trumped up scientific disagreements, but also the problem of modern progress itself. Obesity, anthropocentric climate change, wasting illnesses, ecological degradation, and global famine are often the unintended consequences of unchecked industrial growth, reckless eating habits, and artificially extended lifespans. Only through well-crafted political, regulatory, industrial, and cultural counterstrategies can we change enough minds to check these threats. Big thinking on issues that are usually evaluated separately, this book is sure to scramble partisan divides and provoke unusual, heated debate.